A Legal Protection Effort Workers in Covid-19 - Muhlizar Muhlizar; Syafil Warman; Joharsah (Britain International for Academic Research (BIAR) Publisher, 2023)
Trade unions are formed by workers by ensuring that their position and rights as workers can be balanced with the obligations they perform for employers. In the relationship between workers and employers or employers, it is undeniable that the position of workers is higher. And sometimes it results in the arbitrariness of the employers towards their workers. To reduce and deal with the possibility of this arbitrariness, workers should have an association which is usually called a trade union. with trade unions, workers can unite so as to balance their position with employers. Article 1 paragraph 1 expressly states that a trade/labor union is an organization formed from, by and for workers/laborers both within the company and outside the company, which is free, open, independent, democratic. This study uses a normative juridical approach, namely by collecting, studying and analyzing and understanding law as a set of rules or positive norms in the statutory system that regulates human life. In Law no. 21 of 2000 concerning Worker/Labour Unions spells out what the objectives of trade/labor unions are to provide protection, defend rights and interests, and improve proper welfare for workers/laborers and their families.